Creating joy in the workplace. Issue 145 (December 2021) - Jalilianhasanpour, Rozita; Asadollahi, Shadi; Yousem, David M.
Highlights: A joyful workplace begins with employees committed to its mission, vision, values. The physical and psychological environment contribute to feelings of well-being. Expressions of gratitude, appreciation, and humor engender workplace pleasure. Equitable compensation and recognition for personal contributions please workers. Abstract: Creating a joyful workplace is not the same as dealing with issues of stress, fatigue, burn-out, and resilience. It requires a proactive approach to augment feelings of worth, appreciation, and well-being in the members of the team. The sense that one is pursuing worthwhile, valuable activities requires a wholesale commitment to the mission, vision and values of the organization. These tenets are often created through an organic consensus of collegial workmates and then put to action by a leadership team. Reassessing the goals and virtues of the organization at appropriate intervals leads to ongoing loyalty and commitment to the team and a positive attitude. Well-being is addressed through the creation of a bright and cheerful physical and psychosocial workplace that offers programs that encourage mindfulness, humor, playfulness, and fitful lifestyle choices. The sense that one's work is appreciated and valued stems from an attitude of gratitude on behalf of all levels of the organization including management and peers where such encouragement flourishes. Those expressions of appreciation may be in the form of celebrations in the workplace and/or compensation and benefits that appropriately value the contributions of the employee. The organization's executive team should be dedicated to crafting an environment that leads to delighted, healthy employees.